Optimisation of Distribution Routes: A Case Study - Kampf, Rudolf; Hlatka, Martina; Gross, Patrik (Communications - Scientific Letters of the University of Zilina, 2021)
This article focuses on optimisation of the distribution routes for a company that produces carpets, floor coverings and tapestries. The optimisation process is based on operational research methods including, without limitations, Mayer's method and the single linkage method. The obtained results are subsequently compared to the current situation and evaluated in terms of time and costs. The conclusion provides the optimised economic solution.
Keywords: logistics; transport; transportation problem; operational research; Mayer extasciiacutes method; single linkage method